2008
DOI: 10.3161/00159301ff2008.51.1.015
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito fauna (Diptera: Culicidae) of five different towns in Poland with special reference to the occurence of human disease vectors

Abstract: A bstract: The mosquito fauna has been studied in five Polish towns: Szczecin (31 species recorded), Świnoujście (23)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…All mosquito species collected in this study have been reported in Poland previously [95][96][97]. A significant relationship was noted between average air temperature and dominant mosquito species.…”
Section: Seasonal Dynamics Of Mosquitoes In Western Polandmentioning
confidence: 55%
“…All mosquito species collected in this study have been reported in Poland previously [95][96][97]. A significant relationship was noted between average air temperature and dominant mosquito species.…”
Section: Seasonal Dynamics Of Mosquitoes In Western Polandmentioning
confidence: 55%
“…and Cx. torrentium in Polish cities (Gdańsk, Warsaw, Wrocław, Świnoujście and Szczecin) support the hypothesis of the high probability of the occurrence of WNV in Poland [60,61]. Cx.…”
Section: Chikv Denv Wnv and Zikv Importation And Risk Of Introduction Tomentioning
confidence: 53%
“…Original articles on the occurrence of mosquitoes in Poland published after 2000 come from 15 out of 16 voivodeships (Figure 1, Tables 1-3) and concern mostly data from urban areas, including Wrocław [5,10,[14][15][16][17][18][19][20], Gdańsk, Gdynia, Sopot [21], Krynica Morska [22], Warsaw [23], Poznań [24], and Świnoujście [25]. Additionally, based on literature data, a review of species occurring in five Polish towns (Szczecin, Świnoujście, Gdańsk, Warszawa, Wrocław) was published [26]. Scarce data concern protected areas such as the Narew National Park [27] and the Iława Lakeland Landscape Park [28].…”
Section: Current Knowledgementioning
confidence: 99%
“…Among the mosquito species found in Poland, 40% are potential or documented vectors of pathogens (Table 4) [2,20,26,68]. These species can transmit malaria plasmodia (currently in Poland, only imported malaria cases are reported), arboviruses, or zoonotic parasites.…”
Section: Medical Importancementioning
confidence: 99%